2023
DOI: 10.1007/s42452-023-05310-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of synthesized Au/Ag Nanoparticles using 532 nm and 1064 nm pulsed laser ablation: effect of solution concentration

Abstract: The primary objective of this experimental research is to introduce the capacity of laser irradiation into the synthesis of bimetallic nanoparticles from noble metals. Gold and silver nanoparticles are produced through the laser ablating gold and silver targets in distilled water. Originally, the samples are synthesized by using Nd:YAG laser with 1064 nm wavelength and 7 ns pulse width. Following this, solutions mixed with different volumetric ratios, are irradiated by the second harmonic of the said laser at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
2
2
0
Order By: Relevance
“…Only in the area greater than 400 nm can reveal the peaks related to the bipolar mode. Similar values have been found in similar studies [42,81]. The dipole three plasmon absorption bands detected in the VIS range are shown as s3-s5 (420 nm, 423 nm and 438 nm).…”
Section: Uv-vis Spectrophotometrysupporting
confidence: 90%
See 3 more Smart Citations
“…Only in the area greater than 400 nm can reveal the peaks related to the bipolar mode. Similar values have been found in similar studies [42,81]. The dipole three plasmon absorption bands detected in the VIS range are shown as s3-s5 (420 nm, 423 nm and 438 nm).…”
Section: Uv-vis Spectrophotometrysupporting
confidence: 90%
“…The PL spectrum which is detected near of 528-533 nm ( ~ 2.34-2.32 eV) is also recorded by R. Zakaria et al, for Au and Ag nano-owers around 535 nm (2.31 eV) [32]. In another study, similar peaks were found in the 530-540 nm ( ~ 2.33-2.29 eV) for the Au/Ag bimetallic structure [42]. The interface interaction between Au and AgNPs in PL analysis is observed as a redshift, which represents the interference in terms of LSPR of Au and AgNPs in the bimetallic system.…”
Section: Photoluminescence (Pl) Studiessupporting
confidence: 75%
See 2 more Smart Citations
“…It is worth noting that they studied the effect of laser energy simultaneously with the effect of the medium. In the study conducted by Adib Amini et al [34], solutions with varying volumetric ratios were exposed to the second harmonic of the laser at a wavelength of 532 nm. This laser-induced synthesis process led to the formation of Au-Ag bimetallic nanoparticles.…”
Section: Effect Of Mediummentioning
confidence: 99%